PEMANFAATAN CONTENT MANAGEMENT SYSTEM DALAM PENGEMBANGAN WEBSITE KEBUGARAN (WWW.FITNESSHEALTH.COM) - Supriyanto karya (Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
Currently awareness of a healthy lifestyle has become the needs of society in general, especially for young people. In addition to healthy living, young people also have the motivation to get the ideal body. One way to achieve that goal is to practice in fitness places. Not only that, the nature of young people who like to hang out and open with new communities to make them feel at home for long gym, both for exercise and socializing. The problem is the lack of correct and correct information for people who just want to practice where to go to the gym just sometimes still inferior. The amount of misinformation makes the exercise seem hard to do. One of the best solutions to overcome this is to create a special website that addresses fitness issues. Through this website everyone who wants to maintain health can share information, motivation, education and the right products. This website can also be a place to discuss all things related to fitness such as how a good diet is right, build the desired muscle, as well as supplement-supplement support. As a solution to this problem, researchers designed and developed a fitness web site using the content management system.Â Key Word : Content Management, Website, Fitness Health